Kornilov Arkady Petrovich (1850-1928), Hofmeister, councillor of state, steward of grand duchess Elizabeth Feodorovna: a newfound face - Abroskin, V.N.; Redkina, M.G. (Perm Federal Research Centre Journal, 2022)
The article is timed to the 300th anniversary of the city of Perm (1723–2023). From time immemorial to the present, Perm has been a center of attraction for personalities who have left a noticeable mark in the history of the Russian state. We continue the series of publications started by the journal «Vestnik of the Perm Federal Research Center», № 3, 2021, in order to correct mistakes made by the publisher of the book «Memoirs of the Governor, Perm (1911–1915)». Memoirs of Ivan Frantsevich Koshko, the penultimate Perm governor of the pre-revolutionary period, who was directly involved in the reception of the imperial family during their visit to Perm in July 1914. The task of the study is to identify historical figures by analyzing archival documents, memoirs and opinions of historians, comparing photographic materials of the late 19th – early 20th centuries, to determine the genuine appearance of the people depicted in the photograph, thereby restoring historical truth, «the newfound face», and answering the question – who is who.